Evaluation of Theileria equi vertical transmission rate and routes in a cohort of asymptomatic mares and their foals - Lisa-Marie Hermans; Claire Bonsergent; Anne Josson; Gloria Rocafort-Ferrer; Marine Le Guyader; Sophie Angelloz-Pessey; Agnès Leblond; Laurence Malandrin (Ticks and Tick-Borne Diseases)
Equine piroplasmosis is a tick-borne disease mainly caused by Theileria equi and Babesia caballi. The objectives of this study were to analyse the frequency and routes of vertical transmission of these blood parasites from 179 asymptomatic mares to their foals. Foals were sampled within 72 h post-partum. The seroprevalences determined by Indirect Immunofluorescent Antibody Test (IFAT) and based on a subset sample of 107 couples, were 59.8% and 42.1% for T. equi and B. caballi, respectively in the mare population, and 54.2% and 40.2% in the foal population. A species-specific nested PCR was performed on all blood samples (358) and on available samples of placenta (24), umbilicus (6) and colostrum (18). For mares, 30.2% (54/179) and 2.2% (4/179) were PCR-positive for T. equi and B. caballi, respectively. Vertical transmission was not observed in the case of B. caballi, and four foals were born T. equi PCR-positive, giving a transmission rate of 7.4% (4/54). The blood smear evaluation showed viable T. equi parasites for the four foals without clinical signs of neonatal equine piroplasmosis, but one foal had acute renal failure. Theileria equi DNA was detected in umbilical cords, placenta and/or colostrum from PCR-positive mares, without correlation with the carrier status of the foal. One foal was born carrier but T. equi DNA had not been detected in the placenta. The 18S rRNA genotype E of T. equi was characterized in the four foals, foetal parts of the placenta and colostrum. The routes of transmission and particularly the possibility of colostral passage warrant further investigation.